Dalla pagina alla parete Tipografia futurista e fotomontaggio dada - TOSCHI, CATERINA (Biblioteca di Studi di Filologia Moderna, 2017)
The volume retraces the influence of futuristic typographic experimentalism on the dada photomontage, investigating the progressive transformation of the alphabetical fragment into an image in the research of the first avant-garde movements. Moreover, it analyses the avant-garde reinterpretation of the neue Typographie in central-east-Europe. From the "Words-in-Freedom" to the Lautgedicht, from the Manifesto Poems to the first photomontages, the role of typography in the affirmation of two postulates of the twentieth-century artistic culture is analysed: the use of the word is the form and the value of the procedure is the meaning of the work. A chronology, commented on by photographic and documentary materials, which also offers the reader an instrument of exegesis in synergy with the critical text, paying particular attention to the testimonies of the Dadaists in the context of the neo-avant-garde movement.